2014
DOI: 10.1134/s0020168514100185
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibria and electrical properties of barium-containing relaxor-based solid solutions

Abstract: We have studied the effect of modification with Ba on the phase composition, structure, and elec trical properties of ceramic samples of Pb (1 -x) Ba x (Mg 1/3 Nb 2/3 ) m (Zn 1/3 Nb 2/3 ) y (Ni 1/3 Nb 2/3 ) n Ti z O 3 (0 ≤ x ≤ 0.15) solid solutions and investigated phase equilibria in this system in the range 0 ≤ x ≤ 0.15. The results indicate that a tetragonal and a low symmetry phase coexist in the composition range 0 ≤ x ≤ 0.05, a pseudocubic phase exists in the range 0.05 < x < 0.10, and a cubic phase exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Earlier it was shown that the introduction of 5 mol% Ba 2+ in PZN–PMN–PNN–PT leads to stabilization of the perovskite structure (the traces of pyrochlore phase disappear on X‐ray diagrams), changes in the phase composition of the studied ceramics, significant increase in the values of their piezoelectric and dielectric responses and modifications of microstructure . A preliminary phase diagram of this system with variation in the barium content was constructed . However, the establishment of the MPB on the phase diagram of the system required clarification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier it was shown that the introduction of 5 mol% Ba 2+ in PZN–PMN–PNN–PT leads to stabilization of the perovskite structure (the traces of pyrochlore phase disappear on X‐ray diagrams), changes in the phase composition of the studied ceramics, significant increase in the values of their piezoelectric and dielectric responses and modifications of microstructure . A preliminary phase diagram of this system with variation in the barium content was constructed . However, the establishment of the MPB on the phase diagram of the system required clarification.…”
Section: Introductionmentioning
confidence: 99%
“…28 A preliminary phase diagram of this system with variation in the barium content was constructed. 29 However, the establishment of the MPB on the phase diagram of the system required clarification.…”
Section: Introductionmentioning
confidence: 99%